(untitled) (Bangladesh Journal of Medical Education, 2017)
This study aimed to evaluate the current status of the internship assessment in medical colleges of Bangladesh. Internship acts as the pathway from being a medical student to becoming a registered doctor. Hence, a rigorous and robust internship leads to producing better doctor and in turn better healthcare. Thus, proper assessment is necessary to ensure the quality of the future medical practitioners. Unfortunately, no study has been done in Bangladesh related to this context. A cross-sectional descriptive study with pre-tested self-administered questionnaires covering study place and population and factors relevant to intern assessment (assessment after each major discipline completion, assessment techniques, and feedback) was performed. The study was carried out in 8 medical colleges (4 public and 4 non-government; 4 inside Dhaka and 4 outside). 300 completed questionnaires (250 interns, 50 supervisors) were analyzed. All the collected data were analyzed and presented with SPSS v 19.0 software. Results revealed that there was no assessment present after completion of major placement rotation (about 54% interns and 24% teachers). Furthermore, only logbook was signed as the prevailing assessment technique (more than 66% interns and 72% doctors). Moreover, assessment feedback system was not fully functional (48.7% respondent views). Hence, the overall scenario is shabby and poses questions on our future doctors’ skill set. Bangladesh Journal of Medical Education Vol.8(1) 2017: 14-17